2014
DOI: 10.1039/c4nr02080d
|View full text |Cite
|
Sign up to set email alerts
|

Surface Al leached Ti3AlC2as a substitute for carbon for use as a catalyst support in a harsh corrosive electrochemical system

Abstract: Surface Al leached Ti3AlC2 particles (e-TAC) with high corrosion resistance and excellent electrical conductivity were developed as an advanced support material for Pt catalysts. Electrochemical measurements confirm that the supported Pt/e-TAC electrocatalyst shows much improved activity and enhanced durability toward the oxygen reduction reaction when compared with the commercial Pt/C catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
143
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 261 publications
(151 citation statements)
references
References 26 publications
4
143
0
1
Order By: Relevance
“…Moreover, it was observed that a homogeneous size distribution was achieved without a reducing agent by direct addition of Au salt in dark conditions or by photocatalytic assistance of UV irradiation35. Metal NPs (Pt) were also deposited directly on MXene flakes36. Herein, we propose a general in situ reduction method of noble metal NPs on MXene flakes by direct addition of metal salts in ambient air.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was observed that a homogeneous size distribution was achieved without a reducing agent by direct addition of Au salt in dark conditions or by photocatalytic assistance of UV irradiation35. Metal NPs (Pt) were also deposited directly on MXene flakes36. Herein, we propose a general in situ reduction method of noble metal NPs on MXene flakes by direct addition of metal salts in ambient air.…”
Section: Discussionmentioning
confidence: 99%
“…The best electrocatalyst used for this reaction is the Pt-based material Favilla et al, 2013;Liu et al, 2004); but the limited supply and prohibitive cost of Pt greatly impede the large-scale applications of these renewable energy technologies (Ding et al, 2013;Wu et al, 2011;Xie et al, 2014). Recent attentions gradually move to develop non-precious ORR catalysts, such as transition metal oxides (Andersen et al, 2015;Liang et al, 2011), heteroatom-doped carbon (Inamdar et al, 2013;Yang et al, 2014), and metal-N 4 materials (Kruusenberg et al, 2013;Wei et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The resulting Ti 3 C 2 X 2 sheets possess some extraordinary chemical and physical properties due to the presence of functional groups and site interactions on the Ti 3 C 2 X 2 surfaces [25]. Therefore it has been tentatively investigated in the fields of electrochemistry [26,27] and sorption [25,28,29] because of its hydrophilic surfaces, chemical stabilities and environmental friendliness. Our recent studies have shown that Ti 3 C 2 X 2 -supported Ru-based catalysts exhibit excellent catalytic activity for hydrogen generation from the aqueous phase hydrolysis of NaBH 4 [30] and AB [31].…”
Section: Introductionmentioning
confidence: 99%